Penerapan Setting Kelas Terhadap Fokus Belajar Anak Usia Dini di TK Nurul Latifah - Bella Shintia Dewi; Arie Widyastuti; Nuligar Hatiningsih (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the Application of Classroom Settings to the Focus of Early Childhood Learning in Nurul Latifah Kindergarten. The background of this study is taken from the importance of an organized learning environment to support children's focus in the learning process. This study uses a qualitative analytical descriptive approach to describe situations or events, depending on the focus and objectives of the researcher, the research subjects include the principal, class teachers, and parents in one of Nurul Latifah Kindergarten. Data were collected through observation, interviews and documentation, then analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that the implementation of classroom settings is carried out through classroom arrangement, table and chair arrangement, provision of media appropriate to the theme, lighting and air circulation settings, and structured learning time management. A well- organized classroom setting can improve children's learning focus, characterized by children remaining longer in activities, being actively involved, and completing tasks according to teacher directions. Supporting factors include teacher involvement as a facilitator, relevant media, and consistent class routines. The obstacles faced include limited media, noise disturbances, and differences in focus levels between children. In conclusion, implementing a well-organized, engaging, and child- centered classroom setting has proven effective in improving early childhood learning focus. It is recommended that schools continue to develop a variety of learning media, maintain a distraction-free environment, and involve parents in supporting the habit of focusing on learning from home.